Maintenance solutions for the conservation of sunflower inflorescences - Sanches, Alex Guimaraes [UNESP]; Silva, Maryelle Barros da; Silva Moreira, Elaine Gleice; Martins Cordeiro, Carlos Alberto (United Arab Emirates Univ, 2019)
The sunflower (Helianthus annuus L.) is an ornamental plant of great acceptance in the market, however, as cut flower has its limited useful life, about 3 to 5 days at room temperature. In order to prolong shelf life and preserve post-harvest quality was evaluated the effect of maintenance solutions on sunflower cv. Oasis for 10 days storage at 25 degrees C. O experimento foi conduzido em delineamento inteiramente casualizado em arranjo fatorial 5x6, correspondendo a cinco tratamentos/solucoes de manutencao (distilled water (control), sucrose, citric acid, gibberellic acid and benzylaminopurine to 5%) and six evaluation times (0, 2, 4, 6, 8 and 10 days). The effect of treatments on fresh mass, inflorescence turgescence, stem curvature, relative petal water content, respiratory rate and carbohydrate content was investigated. The results showed that the solutions with sucrose and gibberellic acid significantly (p < 0.05) preserved the quality of the inflorescences as a function of the control of respiratory activity and water absorption, thereby reducing the physiological processes related to senescence. It is recommended to use sucrose 5% as a maintenance solution due to the low cost to producers and consumers.
Keywords: Cut flower; Gibberellic acid; Helianthus annuus L; Sucrose